Pengaruh Literasi Keuangan dan Persepsi Risiko terhadap Keputusan Investasi Mahasiswa Universitas Hindu Indonesia - I Putu Ananta Adnyana Putra; Ni Wayan Alit Erlina Wati; Putu Cita Ayu (UNHI Press, 2026)
Rapid technological advancements and easy access to digital financial services have driven a significant increase in investment interest among college students. This study aims to examine the influence of financial literacy and risk perception on investment decisions among students at the Indonesian Hindu University using the Theory of Planned Behavior framework. The study employed a quantitative method with a sample of 90 accounting students selected through purposive sampling. Data were analyzed using multiple linear regression in SPSS version 23. The results indicate that financial literacy (X1) has a negative and significant effect, while risk perception (X2) has a positive and significant effect on investment decisions. Financial literacy does not necessarily guarantee students’ willingness to engage in direct investment practices. However, on the other hand, risk perception actually encourages students to make more informed investment decisions.